Організаційно-економічні заходи ресурсозбереження в молочному скотарстві - Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Boltianska, Natalia; Комар, Артем Станіславович; Комар, Артем Станиславович; Komar, Artem (Мелітополь: ФОП Однорог Т. В., 2019)
Some ways of increasing the feed and energy value of plant bioresources are considered. Averaged values of the frequency of ultrasound, the time of treatment and the temperature of the suspension are outlined. The perspective directions of further researches are indicated
Keywords: ultrasound; ultrasonic treatment; plant bioresources; frequency; lignocellulose